Pengaruh Model Discovery Learning terhadap Peningkatan Keterampilan Proses Sains Peserta Didik Kelas VIII SMPN 13 Makassar - Nurul Fuada; Hasanuddin Hasanuddin; Muhammad Aqil Rusli (Universitas Negeri Makassar, 2025)
This study aims to determine 1) the level of science process skills of students in classes taught using Discovery Learning models and conventional models, 2) the improvement of science process skills of students taught using Discovery Learning model and conventional model, 3) the effect of using the Discovery Learning model on improving students' science process skills. This research is a Quasi-Experiment using Nonequivalent Control Group Design. The population of all students in class VIII SMP Negeri 13 Makassar consisting of 11 classes totaling 341 students, the sample was selected by purposive sampling with 2 classes, namely class VIII H as a control class with 27 students and class VIII G as an experimental class with 26 students. Data collection was done by giving Pretest and Posttest. Data were analyzed with descriptive statistics and inferential statistics. The results of the analysis showed that 1) the level of science process skills of students taught using the Discovery Learning model is in the high category with an average score of 13.03 and the conventional model is in the medium category with an average score of 9.61, 2) the improvement of students' science process skills after being taught using the Discovery Learning model is in the low category with an average N-Gain score of 0.50 and the conventional model with an average N-Gain score of 0.28 is in the low category, 3) there is an effect of using the Discovery Learning model on the science process skills of students in class VIII SMP Negeri 13 Makassar with the results of hypothesis testing, where tcount = 4.32> ttable = 1.68.